A Study About The Effect of Vitamin e on Hyperlipidemia and Atherosclerotic Lesions in New Zealand White Rabbits Fed With a 1% Cholesterol Rich Diet - Torres, Marysabel; Márquez, Mercedes; Sutil, Rosalía; Carrizales, Maira; Leal, María; Reigosa, Aldo (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The purpose of this study was to determine whether the administration of Vitamin E (200mg/day) for 4 weeks could decrease hypercholesterolemia and inhibit atherosclerosis in male hypercholesterolemic New Zealand White rabbits. Plasmatic Total Cholesterol (TC) and LDL-Cholesterol (LDLc) were determined by enzymatic methods and Vitamin E was determined in plasma by HPLC at weeks 0, 4 and 8. A histopathological study was carried out at week 8 (w8), using a hematoxylin-eosin method. Forty rabbits were divided randomly into 5 groups and fed different diets. These diets included a Normal diet, a 1% Cholesterol rich diet, a Normal diet + Vitamin E and 1% Cholesterol rich diet + Vitamin E. The findings did not show a reduction of Total Cholesterol and LDLc in the groups of rabbits that received Vitamin E (III and IV) at weeks 4 and 8. At the end of the experiment, all the animals were deeply anesthetized with hydrochloride ketamina (60 mg/kg body wt) in order to carry out a histopathological study. Regarding the atherosclerotic lesions, Vitamin E did not induce inhibition of the atherosclerotic plaque development or any modification in the lesion type induced by the hypercholesterolemic diet. In conclusion, the results suggest that additional studies need to be carried out with higher doses and/or treatments for a longer period in order to clarify in detail whether Vitamin E really has a hypocholesterolemic effect and inhibits atherosclerosis